Jackfruit waste and peels: Potential as livestock feed - PRUSTY, S; GENDLEY, M K; SINGH, A K; DUBEY, M; PATIL, P V; SHARMA, V K (The Indian Journal of Animal Sciences, 2024)
Feed and fodder problems could be well-addressed regionally using the vegetable wastes. The vegetable wastes are highly perishable and are very prone to spoilage due to high moisture content. These wastes are dumped in open areas contributing to unhealthy/unhygienic surroundings. One of the unexplored vegetable by-products is Jackfruit waste on which least research has been conducted for its possibility to be included in livestock feed. Jackfruit consumption and processing leads to the generation of enormous amounts of non-edible wastes of peel, central axis, and edible by-products like seed and perianth. Jackfruit peel is a rich source of bioactive antioxidants like vitamin C and beta-carotene, which protect the body against free radicals and strengthen the immune system. It is also rich in various phytonutrients such as alkaloids, lignans, isoflavones, and saponins. Thermal drying, grinding and fermentation with fungi and bacteria have been found effective for the inclusion of Jackfruit waste/ peel in livestock meal.